The Description of Aggressive Behavior in Teens Addicted to Online Game - Trimawati Trimawati; Abdul Wakhid (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Aggressive behavior is a reaction in the form of attacks carried out by individuals on people and objects around them on purpose with the intention of hurting and damaging them. And in recent times aggressive behavior has increased, one of the causes is addiction to online games. Online games are very popular with all people, including teenagers. Long-term use of violent media such as online games can instill a mindset about violent actions and increase aggressive behavior.The research aimed to determine the description of aggressive behavior in online game addiction. This research is a descriptive study with 225 sample.The sample selection techniques using purposive sampling. The measuring instrument used for the level of online game addiction is the Game Addiction Scale (GAS) instrument, then the researchers used the Buss-Perry Aggression Questionnaire Scale (BPAQ) questionnaire to measure the level of aggressive behavior.The data were analyzed using the frequency distribution. Based on the research results, it can be concluded that the higher the online game addiction category, the more likely the aggressive behavior will occur.